Interplay between quorum sensing and metabolism in Pseudomonas aeruginosa - Ruparell, Avika (2012)
The important human pathogen Pseudomonas aeruginosa causes a broad-spectrum of diseases including life threatening infections. A cell density-dependent regulatory network termed quorum sensing (QS) is pivotal in the control of P. aeruginosa pathogenicity, and the signal molecules employed are N-acyl-L-homoserine lactones (AHLs) and the Pseudomonas quinolone signal (PQS). Production of these QS signal molecules (QSSMs) requires precursors including fatty acids, S-adenosyl-L-methionine (SAM) and aromatic amino acids. SAM is derived from the activated methyl cycle (AMC) which is an important pathway dedicated to the degradation of the toxic metabolite S-adenosyl-L-homocysteine (SAH). Through removing the genes encoding the AHL synthases, RhlI and LasI from the complex hierarchical system of P. aeruginosa by expressing them in the heterologous host, Escherichia coli, this study has measured the influence of AHL production upon bacterial metabolism. AHL profiles were broader than previously reported, correlated with a reduction in the intracellular concentrations of several metabolites, and were more pronounced in the E. coli strain producing the LasI synthase than the RhlI enzyme. Production of foreign QSSM synthases had a knock-on effect on the native E. coli QSSM, autoinducer-2 (AI-2). We hypothesize that AI-2 production was significantly reduced since it also requires AMC metabolites for its synthesis. The influence that these metabolic perturbations had on cell fitness was manifest through reduced growth in minimal media. Complementation of growth by exogenously added metabolites confirmed our hypothesis that QSSM synthesis creates a drain on metabolite levels with consequences for cell fitness. Site-directed mutagenesis of key catalytic residues in the QSSM synthases was performed to directly prove that the effects observed were due to the function of the synthases, and not the production of a heterologous protein. Moreover, complete profiling of P. aeruginosa PA01 AHL synthase mutants is unravelling the interrelationship between metabolism and cell-to-cell communication in P. aeruginosa.